Spontaneously Self‐Assembly of a 2D/3D Heterostructure Enhances the Efficiency and Stability in Printed Perovskite Solar Cells. Issue 17 (16th March 2020) - Hu, Jinlong; Wang, Chuan; Qiu, Shudi; Zhao, Yicheng; Gu, Ening; Zeng, Linxiang; Yang, Yuzhao; Li, Chaohui; Liu, Xianhu; Forberich, Karen; Brabec, Christoph J.; Nazeeruddin, Mohammad Khaja; et al.
Abstract: As perovskite solar cells (PSCs) are highly efficient, demonstration of high‐performance printed devices becomes important. 2D/3D heterostructures have recently emerged as an attractive way to relieving the film inhomogeneity and instability in perovskite devices. In this work, a 2D/3D ensemble with 2D perovskites self‐assembled atop 3D methylammonium lead triiodide (MAPbI3 ) via a one‐step printing process is shown. A clean and flat interface is observed in the 2D/3D bilayer heterostructure for the first time. The 2D perovskite capping layer significantly suppresses nonradiative charge recombination, resulting in a marked increase in open‐circuit voltage ( V OC ) of the devices by up to 100 mV. An ultrahigh V OC of 1.20 V is achieved for MAPbI3 PSCs, corresponding to 91% of the Shockley–Queisser limit. Moreover, notable enhancement in light, thermal, and moisture stability is obtained as a result of the protective barrier of the 2D perovskites. These results suggest a viable approach for scalable fabrication of highly efficient perovskite solar cells with enhanced environmental stability. Abstract : A 2D/3D layered heterostructure with 2D perovskites self‐assembled atop 3D MAPbI3 via a one‐step printing process is reported. The 2D perovskite capping layer significantly suppresses nonradiative recombination of the devices, leading to a remarkably high open‐circuit voltage of 1.2 V. Moreover, notable enhancement in light, thermal, and moisture stability is obtained as a result of the protective barrier of 2D perovskites.